A COMPARATIVE STUDY UNDER PROGRESSIVELY FIRST FAILURE CENSORED RAYLEIGH DATA - Prakash, Gyan (Journal of Reliability and Statistical Studies, 2015)
A comparative study presented in this article for two different asymmetric loss functions is based on simulation. Two-parameter Rayleigh model is considered here as the underline model for evaluating the properties of Bayes estimators under progressive first failure censored data. Known and unknown both cases of location parameter are considered here for Bayes estimation of scale parameter.